Evaluation of antibacterial, phytochemical and physiochemical parameters of euphorbia rothiana - SANGEETHA G; MADHU K KAPOOR (International Journal of Pharma and Bio Sciences, 2017)
The use of medicinal plants still plays a vital role to cover basic health needs in both developed and developing countries. The aim of our present study was to evaluate phytochemical constituent, antimicrobial activity and physiochemical properties of Euphorbia rothiana. The phytochemical screening revealed the presence of alkaloid, steroids, cardiac glycosides, phenols, saponins, flavonoid, tanins, terpenoids, quinones, and glycosides. Antibacterial activity of Euphorbia rothiana was studied against various bacteria viz, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Salmonella typhi, Staphylococcus aureus, and Corynebacterium diptheri, by agar cup method. Preliminary phytochemical screening of secondary metabolites of Euphorbia rothiana was carried out for understanding their solvent solubility. Ash value like total ash value, acid insoluble value, water soluble value was found out. Experiments for determining extractive values like alcohol soluble extractive value and water soluble extractive was carried out in this study. Antimicrobial activity results revealed that alcoholic extract has wider range of activity on test organisms than methanolic and aqueous extracts, which indicates that the alcoholic extract may contain the maximum active components. Ampicillin was used as positive control for the study of antibacterial activity.